GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 209 species occurrences available in GBIF matching the query: TaxonKey: Tremarctos ornatus (F. G. Cuvier, 1825). The dataset includes 209 records from 39 constituent datasets: 1 records from ISM Mammalogy Collection. 3 records from MVZ Mammal Collection (Arctos). 1 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 21 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 15 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 5 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 19 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Naturalis Biodiversity Center (NL) - Mammalia. 2 records from Museum of Comparative Zoology, Harvard University. 6 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from iNaturalist Research-grade Observations. 5 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 4 records from Mammals housed at MHNG, Geneva. 1 records from DMNS Mammal Collection (Arctos). 1 records from naturgucker. 1 records from CAS Mammalogy (MAM). 1 records from UMMZ Mammal Collection. 3 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1 records from Tissues Specimens. 2 records from ICN - Universidad Nacional de Colombia. 5 records from LACM Vertebrate Collection. 4 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 6 records from Natural History Museum (London) Collection Specimens. 1 records from Ibaraki Nature Museum, Mammals collection. 22 records from NMNH Extant Specimen and Observation Records. 2 records from Colección Mastozoológica de la Universidad Industrial de Santander. 2 records from LSUMZ Mammals Collection. 1 records from Mammal collection of National Museum of Nature and Science. 1 records from Mammals Specimens. 1 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 5 records from Collection Mammalia SMF. 24 records from AMNH Mammal Collections. 2 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 11 records from Animal Sound Archive. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 5 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 14 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences